2017
DOI: 10.1016/j.ajur.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of treatments for metastatic castration resistant prostate cancer

Abstract: ObjectiveTreatment options for metastatic castration resistant prostate cancer (mCRPC) have expanded rapidly in recent years. Given the significant economic burden, we sought perform a cost-effectiveness analysis (CEA) of the contemporary treatment paradigm for mCRPC.MethodsWe devised a treatment protocol consisting of sipuleucel-T, enzalutamide, abiraterone, docetaxel, radium-223, and cabazitaxel. We estimated number and length of treatments for each therapy using dosing schedules or progression free survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…Despite improvement in surgery, radiotherapy, chemotherapy, and endocrinetherapy, most deaths of patients with prostate cancer (PCa) occurred due to distant metastasis. The bone and lymph node metastases have been recognized the most typical metastatic pattern of extraprostatic tumor spread . Nevertheless, several studies reported that up to 15% of patients with PCa might be affected by atypical metastases at diagnosis, including brain, liver, and lung metastases, etc .…”
Section: Introductionmentioning
confidence: 99%
“…Despite improvement in surgery, radiotherapy, chemotherapy, and endocrinetherapy, most deaths of patients with prostate cancer (PCa) occurred due to distant metastasis. The bone and lymph node metastases have been recognized the most typical metastatic pattern of extraprostatic tumor spread . Nevertheless, several studies reported that up to 15% of patients with PCa might be affected by atypical metastases at diagnosis, including brain, liver, and lung metastases, etc .…”
Section: Introductionmentioning
confidence: 99%
“…Those authors also estimated that 10 cycles of cabazitaxel would cost $46,180 . Another review estimated that the costs for 9.5 cycles of docetaxel or 6 cycles of cabazitaxel were $16,235 and $50,039, respectively …”
Section: Prostate Cancermentioning
confidence: 99%
“…Their cost‐utility model revealed that docetaxel was associated with an incremental cost‐effectiveness ratio (ICER) of £32,706 ($51,028) per QALY gained compared with mitoxantrone. A more recent analysis of Medicare reimbursements for elderly men with metastatic prostate cancer indicated that those who received chemotherapy (either docetaxel or mitoxantrone) had an ICER of $99,146 per life‐year gained compared with those who did not receive chemotherapy (Table ) …”
Section: Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations